DETEKSI YERSINIA PESTIS DAN PATOGEN ZOONOTIK LAINNYA PADA TIKUS DI DAERAH FOKUS PES DESA KAYUKEBEK KABUPATEN PASURUAN - Mulyono, Arief; Hidajat, Muhammad Choirul; Ristiyanto, Ristiyanto; Setyaningtyas, Dian Eka; Wigati, RA; Putro, Dimas Bagus Wicaksono; Joharina, Arum Sih; Pratiwi, Ayu Pradipta; Muhidin, Muhidin; Yuliadi, Bernardus (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2024)
Rats are known as carriers and transmissions of zoonotic diseases. About 60 types of zoonotic diseases that rats can transmit to humans. Some zoonotic diseases are Plague, Leptospirosis, Orthohantavirus infection, and Hepatitis E virus. This research aims to detect the bacteria Yersinia pestis, Leptospira, Hepatitis E virus, and Orthohantavirus in rats in Kayu Kebek Village, Pasuruan Regency. The research design used in this study is descriptive with a cross-sectional approach. The rats were captured for three days, two nights in the house, the neighborhood around the house, and the forest. The captured mice were identified as specimens of blood, spleen, kidneys, and liver. Detection of Yersinia pestis, Leptospira, and Hepatitis E is performed using PCR, while the detection of Orthohantavirus is performed using the ELISA method. A total of 45 mice were trapped, consisting of 2 genera and three species. The zoonotic pathogens detected were Leptospira and hepatitis E. Leptospira viruses were detected in Rattus tanezumi, Rattus tiomanicus, and Niviventer fluvescent. Hepatitis E virus is detected only in R. tanezumi. Transmission of leptospirosis and hepatitis E has the potential to occur in Kayu Kebek Village. Rat control is needed to prevent the transmission of leptospirosis and hepatitis E virus infection, and other zoonotic diseases transmitted by rats.